Climatic Databases as Sources of Actinometric Information for Analysis and use of Solar Resources in Kazakhstan (Journal of Geography and Environmental Management, 2018)
At the present stage, there is a growing need for more accurate information about climate resources ith a high spatial resolution, as well as long historical series of observations to solve applied problems.In this connection, the main modern sources of information that are based on satellite observations and mathematical modeling, such as, NASA Surface meteorology and Solar Energy, METEONORM, SARAH,etc. were analyzed in this article. The main characteristics of the considered climatic bases were given. These kinds of information are also increasingly used in the field of renewable energy, since, on the onehand, they are based on a long period of observation, and, on the other hand, they make it possible to circumvent the problem related to the lack of meteorological stations and their distance from each other.